Innovation, employment growth, and foreign ownership of firms: A European perspective - Bernhard Dachs; Bettina Peters (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
This paper examines how foreign-owned and domestically owned firms transform innovation into employment growth. The empirical analysis, based on the model of Harrison, Jaumandreu, Mairesse and Peters (2008) and CIS data for 16 countries, reveals important differences between the two groups: Due to general productivity increases and process innovation, foreign-owned firms experience higher job losses than domestically owned firms. At the same time, employment- creating effects of product innovation are larger for foreignowned firms. Together with employment-stimulating effects stemming from existing products, they overcompensate the negative displacement effects resulting in net employment growth in foreign-owned firms. However, net employment growth turns out to be smaller in foreign-owned firms than in domestically owned firms.
urn:nbn:de:bsz:180-madoc-332957
Keywords: O31; O33; F23; 330; employment; innovation; foreign ownership; Community Innovation Survey; host country effects